Деякі концептуальні питання синдрому діабетичної стопи - Бойко, В. В.; Логачов, В. К.; Бєрєснев, С. О. (Clinical Endocrinology and Endocrine Surgery, 2008)
The conceptual going is developed near treatment of diabetic foot syndrome festering-necrotizing complications. Application of the improved tactic allowed to reduce lethality from 6,54% to 3% and number of high amputations from 29,4% to 93,8%.